Immunotherapy in advanced cutaneous squamous cell carcinoma: Sydney west cancer network experience. Issue 1 (25th December 2022) - Hasmat, Shaheen; Howle, Julie R.; Carlino, Matteo S.; Sundaresan, Puma; Veness, Michael J.
Abstract: Background: Cutaneous squamous cell carcinoma (CSCC) is the second most common malignancy in the Caucasian population. A minority of cases are inoperable at presentation, recur or develop metastatic disease with a historical 5‐year overall survival of ~10%. Treatment options in this setting are generally palliative. Immunotherapy has emerged as a new paradigm in managing these patients. Methods: Patients presenting to Sydney West Cancer Network with locally advanced or metastatic CSCC treated with the anti‐PD1 agent cemiplimab were identified. Response to treatment was objectively assessed based on RECIST1.1 or PERCIST criteria. Primary end point was objective response rate (ORR). Secondary end points included progression‐free survival (PFS), overall survival (OS), therapy toxicity, and predictors of treatment response. Results: A total of 19 patients were identified with a median age of 76 (range 56–94) and 4 immunosuppressed. The longest follow up duration was 28 months. ORR, complete response (CR), and partial response (PR) were 68% (13/19), 53% (10/19), and 16% (3/19), respectively. Median PFS was 12 months (95% CI 9–14) whilst median OS was not reached by end of study. Responders (CR or PR) had significantly superior OS compared to those with no response ( P  < 0.01). A primary site of head and neck cancer was significantly associated with ORR ( P  = 0.04). A single patient experienced Grade 3 toxicity with the rest being Grades 0–1. Conclusion: This study confirms the clinical efficacy of cemiplimab in patients with advanced CSCC with many experiencing a durable response and an acceptable adverse effect profile. Abstract : Cemiplimab, an immune checkpoint inhibitor, is shown to have clinical activity in more than half patients with advanced cutaneous squamous cell carcinoma not amendable to conventional therapy. A durable response is demonstrated despite patient frailty.